PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM, DANA ALOKASI KHUSUS DAN PRODUK DOMESTIK REGIONAL BRUTO TERHADAP BELANJA DAERAH DI KABUPATEN/KOTA PROVINSI JAWA TENGAH TAHUN 2011-2013 - Yohana Pratidina, 11.05.52.0150; Poerwati, Rr. Tjahjaning (Students Journal of Accounting and Banking, 2016)
This study aims to test the Local Own Revenue, General Allocation Funds Special Allocation Fund and Gross Regional Domestic Product for Regional Shopping in the Regency / City Central Java Year 2011 to 2013.Â The data used is the Local Own Revenue, General Allocation Funds Special Allocation Fund, Gross Regional Domestic Product and Expenditure at District / City Central Java. 105 samples obtained data. The research data were then tested by multiple linear regression.Â The results showed that: Local Own Revenue positive and significant impact on regional expenditures. General Allocation Fund positive and significant impact on regional spending. Special Allocation Fund is not significant positive effect on regional spending. Gross Domestic Product no significant positive effect on regional expenditures.Keywords: Local Own Revenue, General Allocation Fund, Special Allocation Funds, Gross Regional Domestic Product And Expenditure